Analisis Unsur-Unsur Komunikasi - Efendi, Erwan; Dwi, Alya; Adfi, Luthfizha; Fikri, Muhammad; Nadiyah, Ridha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Communication (absorption from Dutch: communicatie) is